Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
1992
DOI: 10.3168/jds.s0022-0302(92)77905-3
|View full text |Cite
|
Sign up to set email alerts
|

Energy Balance and Lactation Response in Holstein Cows Supplemented with Cottonseed with or Without Calcium Soap

Abstract: Holstein cows (n = 58, 21 primiparous), fed corn and wilted grass silages (63:37, DM basis) for free choice consumption, were assigned to control concentrate or supplemented concentrate during wk 1 to 16 postpartum with linted whole cottonseed (15% of projected DMI) alone or with Megalac (.54 kg/d). Our objective was to examine the effects of fatty acids on energy and N balances, total tract digestibility, and milk fatty acids in wk 7 and 16 and to assess total lactation responses. During balance measurements,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

4
21
0
5

Year Published

1995
1995
2015
2015

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 56 publications
(30 citation statements)
references
References 27 publications
4
21
0
5
Order By: Relevance
“…Indeed, some in vitro experiments showed that medium-chain fatty acids (8 to 16 C), such as lauric (C 12:0 ) and myristic (C 14:0 ) acids caused a greater decrease in CH 4 production compared with short (B8 C) or long (]18 C) fatty acids (Dong et al 1997;Dohme et al 2000). Other suggested explanations for depressed CH 4 production due to lipid supplementation include a reduction in the amount of organic matter fermented in the rumen (Holter et al 1992;Johnson and Johnson 1995) and the inhibitory effect of lipids on ruminal microorganisms activity (Ivan et al 2004).…”
Section: Mse06:7mentioning
confidence: 99%
See 1 more Smart Citation
“…Indeed, some in vitro experiments showed that medium-chain fatty acids (8 to 16 C), such as lauric (C 12:0 ) and myristic (C 14:0 ) acids caused a greater decrease in CH 4 production compared with short (B8 C) or long (]18 C) fatty acids (Dong et al 1997;Dohme et al 2000). Other suggested explanations for depressed CH 4 production due to lipid supplementation include a reduction in the amount of organic matter fermented in the rumen (Holter et al 1992;Johnson and Johnson 1995) and the inhibitory effect of lipids on ruminal microorganisms activity (Ivan et al 2004).…”
Section: Mse06:7mentioning
confidence: 99%
“…Seven publications (reporting 25 diets) available in the literature on the effects of lipid supplementation on CH 4 production, milk production, and milk composition of dairy cow were used to build the database ; Van der Honing et al 1981;Holter et al 1992;Sauer et al 1998;Jonhson et al 2002;Dohme et al 2004). In each selected study, there was a control diet [i.e., lower ether extract (EE) content] consisting of a basal diet, and a lipidsupplemented diets (i.e., higher EE content) as dietary treatments.…”
mentioning
confidence: 99%
“…The important question of persistence of the effect of lipids on CH 4 production has not been adequately addressed (Woodward et al, 2006). Some studies do report long-term effects of dietary lipids, but data are inconsistent (Holter et al, 1992;Grainger et al, 2008 and2010b;Grainger and Beauchemin, 2011).…”
mentioning
confidence: 99%
“…Os resultados obtidos estão de acordo com os relatados por Schingoethe & Casper (1991), Holter et al (1992) e Grummer & Melissa (1993), mas divergem dos dados descritos por Canale et al (1990), que, trabalhando com gordura protegida e diferentes níveis de FDN, encontraram aumento do consumo de MS e FDN, tanto em kg/dia quanto em kg/100 kg PV.…”
Section: Resultsunclassified
“…Palmquist (1991) utilizou diferentes fontes e ní-veis de gordura para vacas leiteiras e não encontrou alterações nos percentuais de gordura e proteína no leite. Os dados resultantes do teor protéico do leite, neste experimento, estão de acordo com os encontrados por Stern et al (1985), Holter et al (1992), Deresz et al (1996). Astrup et al (1974), por sua vez, trabalhando com óleos de coco e de soja protegidos, para vacas leiteiras, obtiveram aumento significativo no teor de proteína do leite.…”
Section: Means In the Same Row With Different Superscripts Differ (Punclassified